Practical issues involved with the use of bortezomib (Hematology Meeting Reports, 2009)
The use of proteasome inhibition as a therapeutic target against human cancers represents an exciting new target either alone, or in combination with other agents. The use of single agent bortezomib in relapsed myeloma resulted in a 43% response rate, improved time to progression, and superior overall survival when compared with high dose dexamethasone in the randomized phase III APEX trial. This survival benefit continues to hold despite the cross-over use of bortezomib for patients initially randomized to receive dexamethasone, further solidifying the use of bortezomib as a standard approach for the management of relapsed myeloma.